2018
DOI: 10.1017/s1047951118001774
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in paediatric cardiac ICU patients managed with extracorporeal membrane oxygenation

Abstract: BackgroundVeno-arterial extracorporeal membrane oxygenation is frequently used in patients with cardiac disease. We evaluated short-term outcomes and identified factors associated with hospital mortality in cardiac patients supported with veno-arterial extracorporeal membrane oxygenation.MethodsA retrospective review of patients supported with veno-arterial extracorporeal membrane oxygenation at a university-affiliated children’s hospital was performed.ResultsA total of 253 patients with cardiac disease manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Twenty-six studies ( 2 , 10 34 ) were included in the analysis with a total of 186,648 patients, and the proportion of the population who underwent PC-ECMO was 2.5% (26 studies reporting on 2,683 patients) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six studies ( 2 , 10 34 ) were included in the analysis with a total of 186,648 patients, and the proportion of the population who underwent PC-ECMO was 2.5% (26 studies reporting on 2,683 patients) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dohain et al [ 17 ] reported a 40% survival rate with ECMO, and they declared that the survival rate was higher with biventricular repair. Single ventricular repair is declared as a risk factor for mortality [ 5 , 18 , 19 ] . Although in our study the survival rate with biventricular repair and single ventricular repair were 56.8% and 18.2%, respectively, it did not reach statistically significance ( P =0.055).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings in pediatric patients, they did not observe any differences in mortality or complication rates between the groups. Achuff et al ( 12 ) described a 10-year experience from a single center ( n = 253), examining outcomes for neonatal and pediatric patients placed on ECLS in a cardiac ICU. In a subgroup of patients (those who had not undergone surgery prior to ECLS), they found increased mortality associated with initiation at night or on weekends.…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup of patients (those who had not undergone surgery prior to ECLS), they found increased mortality associated with initiation at night or on weekends. Over half of the patients in that study underwent eCPR ( 12 ). Burke et al ( 11 ) reported outcomes for 53 pediatric patients who underwent eCPR in a single center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation